Quantifying the econometric loss of a cyber-physical attack on a seaport - Tam, Kimberly; Chang, Barbara; Hopcraft, Rory; Moara-Nkwe, Kemedi; Jones, Kevin (Frontiers in Computer Science, 2023)
Recent, and near-future, developments in modern Cyber-Physical Systems (CPS) are significantly increasing the level of automation, intelligence, and optimization capabilities these systems can have. Both creators and adopters of new technologies emphasize the benefits of developing technology: in particular, safety, cost-savings, and efficiencies. However, the majority of literature seems to under-represent the potential risks associated with the adoption of not just individually complex systems, but interconnected Systems-of-Systems (SoS). This may be because near-future research primarily focuses on the potential benefits, but even many recent adoptions have received little rigorous scrutiny. Moreover, these studies that do explore issues, such as cyber-attacks on CPS, often lack an analysis of the potential impact based on the way cyber-physical risks are communicated. Additionally, as there are high levels of interactions and inter dependencies in CPS, disruptions of any kind in one sector can propagate to others. The initial economic impacts of this may start locally but will inevitably have some global effects if response mechanisms prove insufficient. This case study aims to address a research gap in modeling and quantifies how a cyber-attack, with physical consequences, can affect local and global trade if a single maritime port is affected. Furthermore, to understand the public's perception of risk about cyber-attacks, a fairly new threat to global supply chains, members of the public are asked to react to the potential econometric losses. This study produced the five-part CyPEM (Cyber Physical Econometric Model) that has the capability to translate a cyber-attack to an econometric loss. Each framework part may also be swapped out to analyze different CPS.